Konsep Multiple Intelligences Perspektif Munif Chatib Dalam Mengembangkan Sistem Pendidikan Di Indonesia - Fathrizika Ismail, Iffah; , Dra. Mahasri Shobahiya, M.Ag (2016)
The concept of Multiple intelligences shows that is variety of intelligencesbelongs to human beings. Students intelligence can be showed in learning process and in their daily lives. The problem at education institutions today is when new students are recruited in school, in that recruitment the school uses the best input system, what the best input mean here is using formal test, accepting students with high IQ and also seeing the result of the national exams. The challenge in educational institutions in Indonesia today is that the educator can appreciate intelligence among students. Based on that reason, the writer has studied to reformulate the idea of Indonesia figure that is MunifChatib. Trying to formulate Multiple Intelligences concept, being relevant to expectation of nation and state. Hence from that, the writer of the problem statement about "How the Multiple Intelligences concept Munif Chatib perspective in developing education system in Indonesia?". Pursuant to the problem statement, these studies purpose to description Multiple Intelligences concept of MunifChatib perspective in developing education system in Indonesia. This study is using qualitative research method with bibliography research model. While the data collecting technique is using documentation method, and also the data analysis is using content analysis method. The research result shows that Multiple Intelligences concept of MunifChatib perspective in developing education system in Indonesia includes: (1) accepting all students with the intelligences tendency different each other at new student acceptance process in school; (2) checking the condition of students' psychology by using MIR; (3) class division of pursuant to students' intelligences tendency; (4) making new methods and draw pursuant to student tendency; and (5) assessing student from cognitive, psychomotoric, and affective domain. This concept is proved without comparing between one student intelligence and other. The applying from idea of MunifChatib about Multiple Intelligences concept in developing education system in Indonesia, can be seen from school applying that strategy. One of the schools applying the Multiple Intelligences strategy is school of Malik Ibrahim Institution in Gresik.